Pengaruh Kinerja Fundamental Keuangan Perbankan Terhadap Tingkat Suku Bunga Deposito Berjangka Pada Bank Umum Di Indonesia Tahun 2010-2013 - Yusi Lestarina; Restu Agusti; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to examine the effect of the Capital Adequacy Ratio (CAR), the Loan to Deposit Ratio (LDR) and Return on Assets (ROA) on the One Month Deposit Interest Rate In Commercial Banks in Indonesia Year 2010-2013. The population in this study were all commercial banks in Indonesia that is still in operation during the year 2013. The data used in this research is secondary data such as time series data (monthly data) with the research period starting from January 2010 to December 2013. Methods data analysis using multiple linear regression analysis. Based on the analysis, the conclusions of this research are: 1) Variable CAR have negative significant effect on the variable Deposit Interest Rate. 2) Variable LDR have no significant effect on the variable Deposit Interest Rate. 3) ROA have no significant effect on the variable Interest Rate Deposit. The coefficient of determination obtained at 0.084 or 8.4%, which means 8.4% of the causes of the Deposit Interest rate variation is the change in CAR, LDR, and ROA.Keywords: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Assets (ROA) and Deposit Interest Rate